HYPERCHOLESTEROLEMIA IN PATIENTS OF ISCHEMIC STROKE - Saeed, Erum; Ali, Rashid; Jalal-ud-din, Mir; Saeed, Afaf; Jadoon, Raheel Jahangir; Moiz, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Stroke is a common neurological disease that results in significant mortality and morbidity globally. Several risk factors have been identified for stroke among which hyperlipidaemia is one of the modifiable risk factors. Recent clinical trials have showna reduction in ischemic stroke for patients takinglipid lowering medications. Therefore, the aim of this studywas to find out the frequency of hypercholesterolemia in patients of ischemic stroke in Hazara region. Methods: This cross sectional study was carried out in the Medical Department of Ayub Teaching Hospital, Abbottabad. Ninety patients of stroke confirmed as ischemic by CT scan brain were enrolled in the study after informed consent. The frequency of hypercholesterolemia in patients was recorded. Results: There were 55 (61.1%) males. The mean age of patients was 64.4±11.5 years. The mean serum cholesterol in all patients was 4.16±1.1 mmol/l. The mean serum cholesterol of male patients was 4.3±1.2 mmol/l and 4.0±10.9 mmol/l in the case of females. Conclusions: Hypercholesterolemia could not be established as a major risk factor for stroke in our setup through this study that allude to the fact that other risk factors might be contributing more to the incidence of cerebrovascular accident in our population.